The Biodegradation of Soil Organic Matter in Soil-Dwelling Humivorous Fauna - Lou, Xuliang; Zhao, Jianming; Lou, Xiangyang; Xia, Xiejiang; Feng, Yilu; Li, Hongjie (Frontiers in Bioengineering and Biotechnology, 2022)
Soil organic matter contains more carbon than global vegetation and the atmosphere combined. Gaining access to this source of organic carbon is challenging and requires at least partial removal of polyphenolic and/or soil mineral protections, followed by subsequent enzymatic or chemical cleavage of diverse plant polysaccharides. Soil-feeding animals make significant contributions to the recycling of terrestrial organic matter. Some humivorous earthworms, beetles, and termites, among others, have evolved the ability to mineralize recalcitrant soil organic matter, thereby lead to their tremendous ecological success in the (sub)tropical areas. This ability largely relies on their symbiotic associations with a diverse community of gut microbes. Recent genomic studies, as well as metagenomics and proteomics, provide deeper insights into the functions of gut symbionts. In reviewing this literature, we emphasized that in understanding of how these soil-feeding fauna catabolize soil organic substrates not only reveal the key microbes in the intestinal processes, but also uncover the potential novel enzymes with considerable biotechnological interests.